The Sovereignty Aspects In Enactment Of The Apostille Convention In Law No.6 Of 2022 Permenkumham The Analysis Of The Notaries Role For Legalization Of Apostille Public Documents - Kurniawan, Karto; Muda, Iskandar; Bakry, Mohammad Ryan (Universitas Islam Lamongan, 2023)
AbstractGlobal challenges and demands to accelerate economic development are the responsibility of the government in an effort to promote the welfare of society. This also affects the development of relations between citizens. In such a situation of the world community, the legal instruments of international treaties become sacred. The Indonesian government can bind itself to an international treaty in various ways, one of which is by accession. It is expected that an international agreement will become positive law applicable in Indonesia when the agreement applies to Indonesia. Ease of doing business as a key subject in economic development should be encouraged through various aspects of administrative procedures, one of which is the elimination of foreign public document legalization requirements. The presence of Apostille adds to the role of notary as a public official of state administration in the field of law. This research discusses the importance of Indonesia as a participant in the Apostille Convention. It is necessary to reaffirm the role of Indonesian representatives abroad for the legalization of public documents originating from abroad. There is still a need for wider socialization of Apostille legalization. Permenkum HAM Regulation Number 6 of 2022 needa to be followed up with ratification into law.